2019
DOI: 10.1002/jnr.24476
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammation and the gut microbiome in depression and anxiety

Abstract: The study of the gut microbiome has increasingly revealed an important role in modulating brain function and mental health. In this review, we underscore specific pathways and mechanisms by which the gut microbiome can promote the development of mental disorders such as depression and anxiety. First, we review the involvement of the stress response and immune system activation in the development of depression and anxiety. Then, we examine germ‐free murine models used to uncover the role of the gut microbiome i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
201
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(240 citation statements)
references
References 217 publications
3
201
0
6
Order By: Relevance
“…We provide evidence that neurons are enriched for expression of candidate depression risk genes than expected by chance. Our findings highlighted enteric neurons, supporting previous associations between the gut microbiome and mental health 53 . Furthermore, integration of the depression GWAS results and transcriptomic data from brain and non-brain tissues found enrichment in the colon 7 .…”
Section: Discussionsupporting
confidence: 90%
“…We provide evidence that neurons are enriched for expression of candidate depression risk genes than expected by chance. Our findings highlighted enteric neurons, supporting previous associations between the gut microbiome and mental health 53 . Furthermore, integration of the depression GWAS results and transcriptomic data from brain and non-brain tissues found enrichment in the colon 7 .…”
Section: Discussionsupporting
confidence: 90%
“…Lassale et al [43] meta-analysis demonstrated that avoiding a pro-inflammatory diet was associated with a lower risk of depression, supporting the results of the present study. The available research on the relationship between inflammation, intestinal flora, and mental illness such as depression and anxiety has been studied in systematic literature [47]. The result showed that probiotics (intake of good bacteria) and prebiotics (food for the good bacteria) lead to improved intestinal health, which can reduce inflammation and thus result in fewer symptoms of mental illness [47].…”
Section: Discussionmentioning
confidence: 99%
“…The available research on the relationship between inflammation, intestinal flora, and mental illness such as depression and anxiety has been studied in systematic literature [47]. The result showed that probiotics (intake of good bacteria) and prebiotics (food for the good bacteria) lead to improved intestinal health, which can reduce inflammation and thus result in fewer symptoms of mental illness [47]. Foods with a pro-inflammatory effect should be avoided for preventive purposes before and in case of mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Overgrowth of certain bacteria or yeast species can damage the tight-junctions of the lining of the gastrointestinal (GI) tract leading to abnormal serum levels of polysaccharides and other molecules normally confined to the intestinal tract. Inflammatory responses within the GI tract can lead to pathological irritation of the vagus nerve with resulting depressive symptoms (79,80). GI tract inflammation appears to also be capable of inducing CNS inflammation (79).…”
Section: Gut-brain Interactionsmentioning
confidence: 99%